Patient-reported side effects, concerns and adherence to corticosteroid treatment for asthma, and comparison with physician estimates of side-effect prevalence: a UK-wide, cross-sectional study - Cooper, Vanessa (NPJ Prim Care Respir Med, 2015)
BACKGROUND: Non-adherence to corticosteroid treatment has been shown to reduce treatment efficacy, thus compromising asthma control. AIMS: To examine the experiences of treatment side effects, treatment concerns and adherence to inhaled (ICS) and oral corticosteroids (OCS) among people with asthma and to identify the degree of concordance between clinician estimates of side effects and the prevalence reported by patients. METHODS: Asthma UK members were sent validated questionnaires assessing treatment concerns, experiences of side effects and adherence. Questionnaires measuring clinicians’ estimates of the prevalence of corticosteroid side effects were completed online. RESULTS: Completed questionnaires were returned by 1,524 people taking ICS, 233 taking OCS and 244 clinicians (67% of clinicians were primary care nurses). Among people with asthma, 64% of those taking ICS and 88% of those taking OCS reported ⩾1 side effect. People reporting high adherence to ICS (t=−3.09, P<0.005) and those reporting low adherence to OCS (t=1.86, P<0.05; one-tailed test) reported more side effects. There was a disparity between clinicians’ estimates of the frequency of side effects and the frequency reported by people with asthma: e.g., although 46% of people taking ICS reported sore throat, clinicians estimated that this figure would be 10%. Patients who reported side effects had stronger concerns about both ICS (r=0.46, P<0.0001) and OCS (r=0.50, P<0.0001). Concerns about corticosteroids were associated with low adherence to ICS (t=6.90, P<0.0001) and OCS (t=1.71; P<0.05; one-tailed test). CONCLUSIONS: An unexpectedly large proportion of people with asthma experienced side effects and had strong concerns about their treatment, which compromised adherence. These findings have implications for the design of interventions to optimise asthma control through improved adherence.